Candida albicans and Napkin Dermatitis: Relationship and Lesion Severity Correlation - Amani Hussein Karsani; Abdullateef A. Alzolibani; Yasser Farouq; Khalid Zedan; Mohammed Mohsen Alotaibi; Ghada Bin Saif; Ibrahim H. Babikir (Sudan Journal of Medical Sciences)
Introduction: Napkin Dermatitis (ND) is a common problem in infancy that affects almost every child during the early months and years of their lifetime. It is a skin disease that becomes a challenge for both parents and physicians because of its frequency and difficulty in eliminating all of the causative factors in diapered infants. Usually Napkin dermatitis is self-limiting but when associated with Candida albicans (C. albicans) seems to be moderate to severe.